Compact Metamaterial-based Coil Element for Combined 1H/23Na MRI at 7T. (March 2020) - Svejda, Jan Taro; Rennings, Andreas; Erni, Daniel
Abstract: High static magnetic flux densities in the field of magnetic resonance imaging (MRI) allow X-nuclei-based imaging and spectroscopy as well as the utilization of electromagnetic metamaterials. A compact dual-tuned coil element based on a metamaterial transmission line which achieves a quarter-wave resonance at the two distinct operating frequencies of the hydrogen and sodium nuclei is presented. In addition, first combined 1 H/ 23 Na MRI measurement results from a structured phantom are shown and discussed.